Pengaruh Self Efficacy dan Psychological Capital Terhadap Kinerja Pegawai di mediasi Komitmen Organisasional pada Pegawai Sekretariat Daerah Kabupaten Batang - Septa Andi Wibowo; Lie Liana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze efforts to improve employee performance through self-efficacy and psychological capital mediated by organizational commitment. The population in this study was 310 employees of the Batang Regency Regional Secretariat, with a sample size of 110 drawn using the Roscoe formula (1975). Sampling was conducted using purposive sampling with the criterion of employee tenure of more than one year. Data were processed using SPSS version 22 software. Data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F-tests, R2-tests, t-tests, and mediation tests using path analysis. The results indicate that self-efficacy has a positive effect on organizational commitment, psychological capital has a positive effect on organizational commitment, self-efficacy has a positive effect on employee performance, psychological capital has a negative effect on employee performance, organizational commitment has a positive effect on employee performance, organizational commitment mediates the effect of self-efficacy on employee performance, and organizational commitment mediates the effect of psychological capital on employee performance.